The Contribution of DSP Integration to ARM Cores in SBCs for the Video Decoding Process - Ilhan, Hamza Osman; Aydin, Nizamettin (IEEE, 2017)
Today, the ARM processor architectures are used in many electronic devices as the central processing unit. Studies in this field have rapidly progressed because of using ARM architecture in indispensable devices in our daily life such as mobile phones, media players and audio systems. At the same time, users' expectations in this processor are increasing every day. Recently, only the ARM processors cannot achieve these expectations. Therefore, embedded system designers integrate the specific DSP cores next to the processors and named it as System on Chip (SoC). It contains ARM and multiple DSP cores specialty for different tasks. In this study, three SoCs were tested on video decoding process with/without the DSP integrations. The contribution of using DSP were measured by the load on the ARM cores during the encoding video data in several formats.
Keywords: ARM; Digital Signal Processors; Video Decoding; Single Board Computers; System On Chip; Automation & Control Systems; Engineering; Instruments & Instrumentation